Tinggal dan Berbuah dalam Kristus: Hermeneutik Kontekstual Yohanes 15:1-8 di Tengah Kehidupan Pemuda GKST Jemaat Anugerah Lena - Melani Dombo; Naomi Tololiu (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2026)
This article is a hermeneutical reading of John 15:1-8 in dialogue with the lived experiences of the youth of GKST Anugerah Lena Congregation. The study arises from the reality that young Christians live amid social change, economic pressures, and educational and occupational mobility that influence their participation in church life. Previous studies on John 15:1-8 have largely focused on Christology, the symbolism of the vine, and individual spirituality, while the contextual appropriation of the text within church communities has received less attention. This research employs a hermeneutical method with a qualitative-descriptive approach through textual analysis of John 15:1-8 and interviews with church youth. The findings show that Jesus as the True Vine is understood as the source of life, spiritual growth, and fruitfulness. Abiding in Christ is interpreted as a continuous relationship sustained through faithfulness amid life's challenges. Furthermore, fruitfulness is understood not only as an individual spiritual quality but also as participation in ministry, solidarity, and responsibility toward the church community.